Genome-wide association study for anther length in some elite bread wheat germplasm - Xiaopeng SONG; Jie FENG; Zixia CUI; Chuanliang ZHANG; Daojie SUN (Czech Journal of Genetics and Plant Breeding, 2018)
The anther is a crucial organ for the development of the spike in bread wheat (Triticum aestivum L.). Long anthers contain large amounts of pollen grains; thus, they are favourable for cross-pollination and increase resilience against adverse environmental conditions. We conducted a genome-wide association study (GWAS) of anther length in 305 elite wheat lines evaluated during 2013-2015 in two locations and two growing seasons. The mapping panel was genotyped using a high-density Illumina iSelect 90K single nucleotide polymorphism (SNP) array. The GWAS used 18763 SNPs and identified 17 markers associated with anther length in wheat. The loci were mainly distributed across the chromosomes 3A, 3B and 7B. Further studies are required to determine if these are candidate genomic regions of anther length. In addition, anther length had high heritability, and positive correlations between anther length and grain weight per spike were observed.